2021
DOI: 10.1007/s42399-021-00998-x
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-Induced Multisystem Inflammatory Syndrome in a Young Adult: Case Report

Abstract: We describe a case of a previous healthy 20-year-old male athlete who presented with an atypical clinical profile with multiorgan involvement within five weeks after confirmed SARS-CoV-2 infection, suggestive for multisystem inflammatory syndrome (MIS); MIS is a rare, potentially life-threatening complication associated with SARS-CoV-2. MIS shares similar clinical features compatible with several overlapping lifethreatening hyperinflammatory syndromes, such as incomplete Kawasaki Disease (KD) and toxic shock s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In this review, 47 cases (mean age=21; 70% male) of emerging adults with cardiovascular complications in the context of confirmed or suspected hyperinflammatory syndromes and active or previous COVID-19 were identified. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 If not concomitant COVID-19, previous infections typically occurred 3-8 weeks prior to onset of symptoms. 23 , 30 , 32 , 33 , 34 , 40 , 43 , 44 , 45 , 46 , 52 , 53 , 56 Alongside MIS-C/A, cardiovascular presentations/complications included ventricular dysfunction (n=33), tachycardia (n=28), hypotension (n=16), cardiogenic shock (n=14), cardiomyopathy (n=11), including myocarditis and pericarditis, valve insufficiency (n=4), atrial fibrillation (n=2), and non-ST-elevation myocardial infarction (n=2); refer to Supplemental Table S2 for additional case details.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, 47 cases (mean age=21; 70% male) of emerging adults with cardiovascular complications in the context of confirmed or suspected hyperinflammatory syndromes and active or previous COVID-19 were identified. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 If not concomitant COVID-19, previous infections typically occurred 3-8 weeks prior to onset of symptoms. 23 , 30 , 32 , 33 , 34 , 40 , 43 , 44 , 45 , 46 , 52 , 53 , 56 Alongside MIS-C/A, cardiovascular presentations/complications included ventricular dysfunction (n=33), tachycardia (n=28), hypotension (n=16), cardiogenic shock (n=14), cardiomyopathy (n=11), including myocarditis and pericarditis, valve insufficiency (n=4), atrial fibrillation (n=2), and non-ST-elevation myocardial infarction (n=2); refer to Supplemental Table S2 for additional case details.…”
Section: Resultsmentioning
confidence: 99%
“… 148 In the cohort study by Belay et al 148 , mainstay treatments for MIS included intravenous immunoglobulin (IVIG) and steroids. Across the 47 cases included in this review 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 70% (n=33) were treated with steroids (e.g. methylprednisolone, prednisolone, prednisone) and 62% (n=29) with IVIG.…”
Section: Resultsmentioning
confidence: 99%
“…In some pathological conditions, the systemic inflammatory response is not correctly counter-regulated and once it is triggered it cannot be normally contained and switched off. After COVID-19 pandemics we have witnessed the emergence of multisystem inflammatory syndrome in children (MIS-C), a rare post-infectious hyperinflammatory disorder associated with SARS-CoV-2 [ 1 ]. This disorder may also have overlapping features with Kawasaki disease (KD), hemophagocytic lymphohistiocytosis (HLH), and toxic shock syndrome (TSS).…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal (GI) symptoms are also described; a systematic review showed rates of vomiting of 4-9%, diarrhea of 6-13%, and abdominal pain in approximately 4% of infected patients [4]. After the COVID-19 pandemic, we have witnessed the emergence of multisystem inflammatory syndrome in children (MIS-C), a rare post-infectious hyperinflammatory disorder associated with SARS-CoV-2 [5]. This syndrome indicates that the symptoms of SARS-CoV-2 infection are closely related to the status of the host; indeed, the treatment and prognosis of these inflammatory diseases have not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%